Multifaceted Dimensions of Chhath Festival: A Case of Terai, Nepal - Khadka, Bhanu Bhakta; Bhattarai, Prakash Chandra; Thakur, Radheshyam (Janabhawana Research Journal, 2025)
Chhath is an antique popular bi-annual Hindu festival devoted to the God of energy - Sun for sustaining life on the earth. The Hindus worship the sun very enthusiastically and pray for the well-being, success, and progress of their family members, friends, and elders. According to Hinduism, Sun worship is related to healing a range of skin diseases. Given this context, a qualitative inquiry was carried out in Kathmandu to explore the multifaceted dimensions that influenced people to celebrate it from time immemorial. Data were collected and interpreted through cultural diffusion theory. The finding shows that this festival has not only economic, socio-cultural but also spiritual, scientific aspects so it has gained much popularity from past to present.